1999
DOI: 10.1346/ccmn.1999.0470412
|View full text |Cite
|
Sign up to set email alerts
|

Preferred Orientation of Phyllosilicates in Gulf Coast Mudstones and Relation to the Smectite-Illite Transition

Abstract: Abstract--Development of preferred orientations of illite-smectite (I-S) has been studied using X-ray diffraction (XRD) texture goniometry to produce pole figures for clay minerals of a suite of 16 mudstone samples from a core from the Gulf Coast. Samples represent a compaction-loading environment in which the smectite-to-illite (S-I) transition occurs. In five shallow, pre-transition samples, there is no significant preferred orientation for smectite rich I-S. Development of preferred orientation of I-S, alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…According to our thinking, the preferred orientation of clay minerals which known for a long time to be the major source of shale anisotropy (e.g. Oertel and Curtis, 1972;Wenk, 1985;Ho et al, 1999 andDay-Stirrat et al, 2008) imparts a preferential direction for the pore-like cracks in between parallel to the bedding directions causes shale to behave like a TI media (Transversely Isotropic Media) where the bedding plane is the plane of isotropy.…”
Section: Resultsmentioning
confidence: 99%
“…According to our thinking, the preferred orientation of clay minerals which known for a long time to be the major source of shale anisotropy (e.g. Oertel and Curtis, 1972;Wenk, 1985;Ho et al, 1999 andDay-Stirrat et al, 2008) imparts a preferential direction for the pore-like cracks in between parallel to the bedding directions causes shale to behave like a TI media (Transversely Isotropic Media) where the bedding plane is the plane of isotropy.…”
Section: Resultsmentioning
confidence: 99%
“…As such, the extent of clay alignment can reflect the potential seal quality. Several studies on the Gulf of Mexico mudstones (Freed and Peacor, 1989;Ho et al, 1999;Aplin et al, 2003) show the concomitant relation between sealing effect and enhanced-clay fabric. Therefore, where diagenesis is not dominant, zones of enhanced microfabrics in mud-prone MTDs can play an important role in creating an effective sealing surface for fluids in the subsurface.…”
Section: Chapter 6: Discussion and Conclusionmentioning
confidence: 99%
“…We propose that zones with enhanced-clay fabric in MTDs play a key role in creating effective hydrocarbon-sealing facies. Previous studies in the Gulf Coast mudstones (Freed and Peacor, 1989) and North Sea siltstones (Nadeau, personal communication in Ho et al, 1999) have shown the concomitant relationship between sealing effect and clay fabric development via smectite-illite (S-I) transformation.…”
Section: Chapter 1: Introductionmentioning
confidence: 95%
“…The microfabric anisotropy of phyllosilicate-rich sediments generally increases during burial and progressive compaction in marine environments (e.g., Bennett & Hulbert, 1986;Day-Stirrat et al, 2012;Ho et al, 1999), of course, also depending on mineral composition and distribution (e.g., Sintubin, 1994). This can be determined indirectly by, for example, AMS (anisotropy of the magnetic susceptibility) measurements, void ratios, or preferred alignment of larger grains, for example, illite flakes (e.g., Agar et al, 1989;Bowles et al, 1969;Kawamura & Ogawa, 2004;Kawamura, 2010;Maffione & Morris, 2017;Schumann, Stipp, Leiss, et al, 2014) or by analyzing crystallographic preferred orientations using diffraction techniques (e.g., Aplin et al, 2006;Day-Stirrat et al, 2012;Kopf & Behrmann, 1997;Schumann, Stipp, Leiss, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%